STRATEGI PEMASARAN JASA PADA PT BANK “X” CABANG PALEMBANG DI BIDANG PENGUMPULAN DANA - Sunardi Selamat (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2018)
The competition that occurred in the Indonesian banking industry became more stringent since the government issued the packages of deregulation banking sector in October 1988 (Pakto 1988). Financial policies become better known to the public, which among others provide convenience to private banks and permit to foreign banks to conduct joint ventures with local banks in the opening of banks both in terms of capital and from licensing. With the wisdom of the Pakto, the number of banks in Indonesia became drastically increased from 124 in 1988 to 240 in 1996, while the number of bank branches grew dramatically from 1,900 to over 6,000 ( Bank Indonesia, 1996). The above marketing strategy consists of three fundamental steps, first identifying and forming a separate group of buyers who need the product or the marketing mix itself (segmenting), the second is the action to select one or More market segments to serve (targeting) and the third step is the act of building and communicating the essential benefits of the products offered to instill a positive impression on the customer's mind (positioning).